Crystal structures of glycoprotein D of equine alphaherpesviruses reveal potential binding sites to the entry receptor MHC-I - Kremling, Viviane; Loll, Bernhard; Pach, Szymon; Dahmani, Ismail; Weise, Christoph; Wolber, Gerhard; Chiantia, Salvatore; Wahl, Markus C.; Osterrieder, Nikolaus; Azab, Walid (Frontiers in Microbiology, 2023)
Cell entry of most alphaherpesviruses is mediated by the binding of glycoprotein D (gD) to different cell surface receptors. Equine herpesvirus type 1 (EHV-1) and EHV-4 gDs interact with equine major histocompatibility complex I (MHC-I) to initiate entry into equine cells. We have characterized the gD-MHC-I interaction by solving the crystal structures of EHV-1 and EHV-4 gDs (gD1, gD4), performing protein-protein docking simulations, surface plasmon resonance (SPR) analysis, and biological assays. The structures of gD1 and gD4 revealed the existence of a common V-set immunoglobulin-like (IgV-like) core comparable to those of other gD homologs. Molecular modeling yielded plausible binding hypotheses and identified key residues (F213 and D261) that are important for virus binding. Altering the key residues resulted in impaired virus growth in cells, which highlights the important role of these residues in the gD-MHC-I interaction. Taken together, our results add to our understanding of the initial herpesvirus-cell interactions and will contribute to the targeted design of antiviral drugs and vaccine development.